Kata Panggilan dalam Masyarakat Melayu: Analisis Sosiolinguistik dan Pragmatik (Jurnal Bahasa, 2002)
This article discusses the expression of respects (the birth rankor the baby names) among the siblings and the older generation in the Malay family. Modernization that surrounds the Malay society seems to have an impact in the use of these expressions. The expressions uncles/aunties, grandma/grandpa have been creeping in the Malay expression of respects. This will eventually erode the usage of the expression of respects system, which is unique to the Malay language that never occurs in any other languages. The authors adopt a multianalysis is also given. This is the part where the impact of modernization is comprehensively decribed.